Representative Sheikh Salman Al-Zahir Al-KhuzaieAnd his political role in the Constituent Assembly and the Iraqi Parliament (1921-1926) (Journal of Imam Al-Kadhim College, 2024)
Representative Salman Al-Zahir is one of the names that cannot be overlooked when discussing the modern and contemporary history of Iraq and the resistance movement against foreign occupation of Iraq, particularly in the regions of the Middle Euphrates over the years, especially in the early 20th century. The idea of "foundation and resistance" resonated deeply with him, manifesting in his actions and behaviors, and was expressed through tangible and clear contributions. These contributions were considered among his most significant in the field of thought and the establishment of Iraq post-British occupation.Discussing the history of Iraq at the beginning of the establishment of the Iraqi Kingdom is incomplete, does not reach its full scope, and does not achieve its scientific and social goals without mentioning the sheikhs of the Middle Euphrates, among whom is Sheikh Salman Al-Zahir Al-Khuzai. He was a product of the central environment and the school of guesthouses in the Iraqi countryside. He realized early in his life the necessity of establishing an Iraqi entity that could keep pace with the developments in the region and the world, especially after the end of World War I (1914-1918), the formation of the League of Nations in 1919, and the introduction of human rights issues. This realization led to his participation in the committees of the Constituent Assembly and the Iraqi Parliament from 1922-1926 to draft the Basic Law for the State of Iraq during the monarchy.   Sheikh Salman Al-Zahir made significant contributions to the Iraqi project of building the Kingdom of Iraq during the reign of King Faisal I under the British Mandate over Iraq (April 25, 1920 - 1932). This followed the formation of the "Tribal Representatives Bloc" based on a proposal by King Faisal, who emphasized the need to involve tribal leaders in the constituent and parliamentary councils. This stemmed from his desire to establish good relations with all influential Iraqi elites to build the new Iraqi state. As evidence, the Iraqi Constituent Assembly included representatives from all Iraqi groups and ethnicities, and the representatives exerted great efforts in drafting the first Basic Law for Iraq in nearly a year. The third ministry of Al-Naqib set October 24, 1922, as the starting date for elections for the Iraqi Constituent Assembly, according to the system issued on March 4, 1922. The Assembly's tasks were defined in three points: drafting a constitution (the Basic Law) for the Kingdom of Iraq, enacting a law for the House of Representatives, and ratifying the British-Iraqi agreement. However, the Iraqi opposition, consisting of religious leaders, intellectuals, and party leaders, rejected this entirely.